ELEVATED UNCONJUGATED BILIRUBIN IN SCHIZOPHRENIC PATIENTS - Ilhamuddin Aziz; Yuyun Widaningsih; Rosdiana Natzir; A. Jayalangkara Tanra (Nusantara Medical Science Journal, 2018)
Strategies for schizophrenic treatment still have been developed in order to increase their effectively, based on latest findings in the etio-pathology. Coincidence of hyperbilirubinemia, especially related to Gilbert’s Syndrome (GS), and schizophrenia/other psychiatric disorders, was reported in several studies although the pattern of this alteration is still controversial.  Bilirubin could induce microglia to release pro-inflammatory cytokine that cause neuroinflammation, one of hypothetic etio-pathogenesis has been the most extensively studied recently. However, no data have been presented about this phenomenon in Indonesia. Therefore, this study aims to investigate plasma bilirubin concentration in psychotic spectrum.This study is cross sectional design that we examined both the total bilirubin and direct bilirubin of every psychotic patient admitted for the first time to Rumah Sakit Khusus Daerah (RSKD) Provinsi Sulawesi Selatan over a period of July—December 2012, by using health people as control. Diagnostic determination was set based on International Classification of Diseases (ICD) 10. Patients suffering from any disease such as anemia (decreased hemoglobin), liver diseases (elevated liver enzymes), or substance abuse were excluded.            From 73 samples, we found that plasma UCB level was significantly elevated, higher in psychotic patients, especially schizophrenic group, than in the control. Total bilirubin rate was slightly increased in schizophrenic group compare to the others and two samples in this group showed hyperbilirubinemia. Further investigations are needed to ensure that whether the elevated UCB was related to GS and whether this condition has inflammatory effect.